Phospholipase C-mediated hydrolysis of phosphatidylcholine is a target of transforming growth factor beta 1 inhibitory signals. - Diaz-Meco, M T (1992)
Cell growth and tumor transformation can be restrained in certain cell systems by the action of transforming growth factor beta (TGF-beta). It has been established that the mechanism whereby TGF-beta 1 inhibits cell growth does not interfere with the triggering of early mitogenic signal transduction mechanisms. Phospholipase C-catalyzed hydrolysis of phosphatidylcholine (PC) is a relatively late step in the cascade activated by growth factors. Therefore, conceivably activation of phospholipase C-catalyzed hydrolysis of PC could be the target of TGF-beta 1 action. In the study reported here, we demonstrate that TGF-beta 1 inhibits the coupling of ras p21 to the activation of PC hydrolysis, which appears to be critical for the antiproliferative effects of TGF-beta 1.